EVALUATION OF UMRAH SERVICE POLICY AT THE REGIONAL OFFICE OF THE MINISTRY OF RELIGIOUS AFFAIRS OF MALUKU PROVINCE - Mohamad Arsad Rahawarin; Ahmad Rosandi Sakir (PT. Banjarese Pacific Indonesia, 2026)
This study evaluates the umrah service policy implemented by the Regional Office of the Ministry of Religious Affairs of Maluku Province. The research was motivated by the need to ensure that umrah services provide protection, convenience, administrative certainty, and equitable access for prospective pilgrims in an archipelagic province. A qualitative descriptive approach was used. Data were collected through observation, document review, and in-depth interviews with officials and employees involved in umrah service management at the Regional Office during August-October 2023. The analysis applies six public-policy evaluation criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The findings show that the policy has generally met the six criteria. Effectiveness is reflected in administrative preparation, document control, security, and comfort before departure, during the stay in Saudi Arabia, and during return. Efficiency is shown through the use of available resources, a service process of approximately three to ten days, and continuous monitoring of travel providers. Adequacy is reflected in supervision of facilities, accommodation, safety standards, information, and complaint mechanisms. Equity is pursued through equal access, affordable costs, gender sensitivity, and protection of pilgrims. Responsiveness appears in rapid responses to complaints, emergency coordination, and service improvement based on feedback. Appropriateness is demonstrated through compliance with Islamic values, business ethics, regulations, and Saudi Arabian procedures. The study implies that digital registration, transparent quota management, cost audits, emergency response teams, and certified service personnel are needed to strengthen umrah service governance.